Research on Object Defect Detection of Automated Pipeline Based on Cognex Camera - Luo, Jie; Ye, Jufeng (Frontiers in Computing and Intelligent Systems, 2024)
With the continuous improvement of people’s living standards, higher requirements have been put forward for the efficiency of the manufacturing industry, so the application of automated pipeline in enterprises is becoming increasingly widespread. Due to various factors such as environment, labor, and technology that affect the manufacturing process of goods, some products have defects. It is necessary to screen out defective products in automated pipeline. This paper investigates the application of Cognex cameras in object defect detection on automated pipeline. The camera obtains material images under backlight conditions to determine the type, defect, color, and position parameters of the material. By analyzing these parameters, it determines whether the material is a qualified part. The results show that the camera can effectively complete the task of object defect detection.